Biocontrol strategies for Mediterranean-style fermented sausages. (January 2018) - Oliveira, Márcia; Ferreira, Vânia; Magalhães, Rui; Teixeira, Paula
Abstract: Naturally fermented meat sausages have a long tradition in Mediterranean countries and are one of the most important groups of traditional foods consumed throughout Europe. Despite all the advances in food science and technology and increased regulatory requirements and concerns for safety and quality during the last decades, the challenge to control important foodborne pathogens in this type of meat products still persists. Simultaneously, growing consumer interest in safe, high quality and minimal processed products, with less additives/preservatives have driven the food industry and scientists in a crusade for innovative technologies to maintain the safety of these products by natural means. Biological control (biocontrol) fits well within this tendency. This review summarizes the latest achievements on biocontrol strategies applied to Mediterranean-style fermented sausages, namely: (i) bioprotective cultures; (ii) bacteriocins; and, (iii) essential oils (EOs). Graphical abstract: Highlights: Biocontrol agents to improve food safety of Mediterranean fermented meat sausages Application of protective cultures with inhibitory activity against pathogens Biocontrol by of bacteriocin incorporation, alone or combined with other hurdles Essential oils as natural antimicrobials effective against unwanted bacteria